Effect of olive leaves addition during the extraction process of overmature fruits on olive oil quality - Malheiro, Ricardo (2016)
The harvest period is one of the most important factors influencing olive oil quality. This period is extended for several months and the late-extracted olive oils are characterized by quality loss and reduced resistance to oxidation. The aim of this work was to verify the effect of olive leaves addition during the oil extraction process in the olive oils quality and composition. In two consecutive years (2009 and 2010), different olive leaves amounts (1%, 2.5%, 5% and 10% w/w) were added during the extraction process of cv. Cobrançosa olive fruits, collected in the late season. Standard quality parameters, oxidative stability, fatty acids profile, tocopherols, chlorophylls, and carotenoids contents were evaluated. Olive leaves addition induces a slight increase in acidity, peroxide value, K232, and K270 without compromising olive oils classification, but the resistance to oxidation was significantly improved. Vitamin E increased nearly 30% with 10% of leaves added mainly due to the considerable increase in α-tocopherol. A similar effect was observed in the contents of chlorophylls (chlorophyll a and pheophytin a) and carotenoids (lutein and β-carotene), that attributed a more intense greener pigmentation and enhanced nutritional attributes. Significant correlations were observed for several parameters with the amounts of leaves added. Moreover, leaves addition modified the characteristics and composition of the olive oils in a way that was possible to discriminate and to classify each group.